Ideals and political participation of the young university students in Lima, in the election process in 2016 - Loayza Javier, Jerjes (2020)
The elections held in 2016 to designate both the new president and the respective congressmen were the starting point for the application of semi-structured interviews that deepened the meaning of politics by the youth population in Lima. Through the university youth discourse reflections known at the time, the statements about politics and its necessary restoration have been detailed. The consulted university youth has an active participation around the institutional change of their respective university representatives, so they visualize a different and renewed policy. In summary, it is concluded that this is an avid approach to migrate towards new ways of redesigning politics in Peru.